Some blood biochemical indices and fertility following treatment of anestrus in Murrah buffaloes - RATHOUR, K K; PANDIT, R K; AGARWAL, R G; QUADRI, M A; SHRIVASTAVA, O P (The Indian Journal of Animal Reproduction, 2023)
The efficacy of some of the hormonal and non-hormonal drugs for the treatment of anestrus, their effect on cenain bloodbiochemical indices and conception rate in 36 Murrah buffaloes were studied. The overall mean values of calcium, inorganicphosphorus, total protein were 6.09:t0.55 mg per cent/3.18±0.31 mg per cent / 5.75±0.23 g per cent, respectively, in the anestrusanimals. The values elevated significantly (P < 0.01) in the post treated animals Ill the ti~ expreuiOA of esuusto 9.20±0.42 mgper cent, 5.28:t0.25 mg per cent/ 7.46:t0.17 g per cent, respectively. The animals expressing estrus following different treatmentswere 66.66 per cent within the duration of 9.60:t:2.44 days. The overall conception rate was 65.33 per cent. The maximum numberof expressed animals resulted in estrus in PMSG group (83.33%) and 60.00 per cent concentration. The maximum number of animalsconcejved in GnRH and progesterone treated groups (75.00 per cent), whereas estrus expression in these groups was only 66.66 percent. In the Lugol's iodine treated group 50.00 per cent animals expressed estrus and 66.66 per cent of them conceived.
Keywords: Anestrus; biochemical indices; treatment; fertility; Murrah buffalo